Recent application and developments of the Biobead system - Cantwell, A. D. C.; Mosey, F. E. (Cranfield University, School of Water Sciences, 1999)
This paper describes the background of recent engineering changes to the BiobeadTM system. In particular known design pitfalls are described. The development of technically improved aeration and flow distribution methods are outlined. The extension of the system to combined C & N removal is outlined together with some recent experimental data which shows higher than expected de-nitrification performance. The benefits of a pre-filtration before the aerated part of the media bed is apparent particularly when removal of industrially derived COD is required to reach UWWT directives standards. This method also allows tertiary treatment of high influent solids whilst maintaining Ammonia removal.